The 2014-16 Oil Price Collapse in Retrospect : Sources and Implications - Stocker, Marc; Baffes, John; Some, Y. Modeste; Vorisek, Dana; Wheeler, Collette M. (World Bank, Washington, DC, 2018)
With the benefit of hindsight, this paper provides a fresh and comprehensive look at the causes of the 2014-16 collapse in oil prices and its impact on the global economy. It disentangles the contribution of supply and demand factors, assesses the impact on activity in oil exporters and oil importers, and reviews policy responses in these countries. The main conclusions are: (i) the decline in oil prices was predominantly triggered by supply factors, particularly rapid efficiency gains in U.S. shale oil production, but softening demand prospects played a substantial role as well; (ii) the short-term benefits of falling oil prices for the global economy were muted by economic rebalancing in China, a low responsiveness of activity in other oil-importing emerging markets, and a sharp slowdown in U.S. investment as energy sector activity declined and a the U.S. dollar strengthened; (iii) oil exporters with flexible exchange rates and relatively large fiscal buffers fared better than others, but most oil-exporting economies still face significant policy challenges as their medium-term prospects for growth and fiscal revenues have deteriorated; (iv) fundamental changes in the oil market make a return to the oil price levels of the early 2010s unlikely, pointing to the need for accelerated reforms, particularly among oil exporters.